Migrasi dan Pembentukan Komunitas: Dinamika Sosial Nelayan Migran Buton di Pulau Derawan - Jaya, Ichwanul; Lampe, Munsi; Abdullah, Suparman (LPPM Institut Pendidikan Nusantara Global, 2025)
Internal migration among coastal communities is often viewed purely through an economic lens. In contrast, in reality, it involves complex social, cultural, and institutional dimensions that shape the formation of migrant communities. The Butonese fishing community on Derawan Island, Berau Regency, exemplifies how migration creates new social spaces rich in meaning, identity negotiation, and structural tensions. This study analyzes the migration process of Butonese fishers to Derawan Island. It explores how they establish a new community through social adaptation and the reproduction of cultural values, while also identifying structural challenges in integrating with local systems. Using a qualitative ethnographic approach through participant observation, in-depth interviews, and oral history documentation across five coastal villages, the study draws on Pierre Bourdieu’s theory of cultural capital, Fredrik Barth’s theory of ethnic boundaries, and Henri Lefebvre’s theory of the production of space. Findings indicate that migration occurred gradually through social networks, driven by ecological pressures, cultural values surrounding migration, and the desire to build a more stable livelihood. The Butonese community reproduces its social structure through collective labor, informal authority, and the creation of symbolic spaces known as the “Buton Group.” Despite achieving internal cohesion, they continue to face structural obstacles, including limited access to land legality, administrative recognition, and formal empowerment programs. This research underscores the need to understand coastal migration not merely as an economic or demographic movement, but as a socially embedded process involving identity, power, and spatial transformation.